The metaphysics of meaning - Katz, Jerrold J. (Cambridge Bradford Books, 1990)
Jerrold J. Katz offers a radical reappraisal of the "linguistic turn" in twentieth-century philosophy. He shows that the naturalism that emerged to become the dominant philosophical position was never adequately proved. Katz critiques the major arguments for contemporary naturalism and develops a new conception of the naturalistic fallacy. This conception, inspired by Moore, explains why attempts to naturalize linguistics and logic, and perhaps ethics, will fail. He offers a Platonist view of such disciplines, justifying it as the best explanation of their autonomy, their objectivity, and their normativity.Jerrold J. Katz is Distinguished Professor of Philosophy and Linguistics at the Graduate Center of the City University of New York.